Green Business Practices for Software Development Companies: An Explorative Text Analysis of Business Sustainability Reports - Sambhanthan, A.; Potdar, Vidyasagar (IGI Global, 2015)
This paper reports the findings of a text analysis of the corporate sustainability reports of eleven large scale Indian Software Development Businesses for the period of 2012 to 2014. The results shows that there are twenty two reported components of software development sustainability namely green buildings, green energy, green factory, green data centres, green infrastructure, green initiatives, green innovation, green packaging, green portfolio, green power, green practices, green procurement, green products, green program, green rating, green solutions, green space, green team, green tech and green supply chain which are addressed in the published reports of Indian software development businesses. The reports were further analysed to infer some knowledge on how the software development companies could contribute to green environment and the possible environmental impacts of these contributions. Finally a number of generalised conclusions were derived and followed by a set of implications for best practices in green software development as the outcome of the research reported in this paper.